A Cell Extraction Method for Oily Sediments - Lappé, Michael; Kallmeyer, Jens (Frontiers in Microbiology, 2011)
Hydrocarbons can be found in many different habitats and represent an important carbon source for microbes. As fossil fuels, they are also an important economical resource, through natural seepage or accidental release they can also be major pollutants. DNA-specific stains and molecular probes bind to hydrocarbons, causing massive background fluorescence and thereby hampering cell enumeration. The cell extraction procedure of Kallmeyer et al. (2008) separates the cells from the sediment matrix. In principle, this technique can also be used to separate cells from oily sediments, but it is not optimized for this application. Here we present a modified extraction method in which the hydrocarbons are removed prior to cell extraction. Due to the reduced background fluorescence the microscopic image becomes clearer, making cell identification and enumeration much easier. Consequently, the resulting cell counts from samples treated according to our new protocol are significantly higher than those treated according to Kallmeyer et al. (2008). We tested different amounts of a variety of solvents for their ability to remove hydrocarbons and found that n-hexane and – in samples containing more biodegraded oils – methanol, delivered the best results. However, as solvents also tend to lyse cells, it was important to find the optimum solvent to sample ratio, at which hydrocarbon extraction is maximised and cell lysis minimized. A ratio between slurry and solvent of 1:2 to 1:5 delivered the highest cell counts without lysing too many cells. The method provided reproducibly good results on samples from very different environments, both marine and terrestrial.